Time Travel to the Past of Bosnia and Herzegovina through Virtual and Augmented Reality - Rizvić, Selma; Bošković, Dušanka; Okanović, Vensada; Kihić, Ivona Ivković; Prazina, Irfan; Mijatović, Bojan (Applied sciences, 2021)
Bosnia and Herzegovina (BH) has a very picturesque past. Founded in 11th century, it has always been a crossroads of faiths and civilizations. Extended Reality (XR) technologies can finally take us to time travel into this history, enable us to experience past events and meet historical characters. In this paper, we overview the latest applications we developed that use Virtual Reality (VR) video, Virtual and Augmented Reality (AR) for interactive digital storytelling about BH history. “Nine dissidents” is the first BH VR documentary, tackling a still tricky subject of dissidents in the Socialist Yugoslavia, artists and writers falsely accused, persecuted and still forbidden. “Virtual Museum of Old Crafts” aims to present and preserve crafts intangible heritage through Virtual Reality. “Battle on Neretva VR” is recreating a famous WWII battle offering the users to experience it and meet comrade Tito, the commander of the Yugoslav Liberation Army. “Sarajevo 5D” shows the cultural monuments from Sarajevo that do not exist anymore in physical form using Augmented Reality. Through user experience studies, we measure the user immersion and edutainment of these applications and show the potential of XR for the presentation and preservation of cultural heritage.